Metabolomic profiling and antibacterial efficacy of probiotic-derived cell-free supernatant encapsulated in nanostructured lipid carriers against canine multidrug-resistant bacteria - Myo, Nay Zin; Kamwa, Ratchnida; Jamnong, Thitirat; Swasdipisal, Busaba; Somrak, Papavarin; Rattanamalakorn, Phanchompoo; Neatsawang, Vipada; Apiwatsiri, Prasert; Yata, Teerapong; Hampson, David J.; Prapasarakul, Nuvee (Frontiers in Veterinary Science, 2025)
AimThis study aimed to investigate the antibacterial efficacy of probiotic-derived cell-free supernatants (CFS) encapsulated within nanostructured lipid carriers (NLCs) against multidrug-resistant Pseudomonas aeruginosa and Staphylococcus pseudintermedius. Additionally, it aimed to identify specific bioactive compounds that contribute to the reported antibacterial properties by characterizing the metabolite substances present in the CFS using a metabolomic analysis technique.MethodsEight strains of lactic acid bacteria including Lactiplantibacillus plantarum (L22F and L25F), Pediococcus acidilactici (P72N, BF9, BF 14, BYF 20 and BYF 26) and Ligilactobacillus salivarius (BF 12) were selected as probiotic candidates. The inhibitory activity of their cell free supernatant (CFS) was tested against clinical strains of P. aeruginosa and S. pseudintermedius isolated from skin wounds of dogs and cats. An untargeted metabolomic approach based on liquid chromatography-mass spectrometry (LC-MS) identified potential antibacterial metabolites in the CFS. Cell-Free Supernatants-Nanostructured Lipid Carriers (CFS-NLCs) were developed, and their antibacterial activity and minimum bactericidal concentration (MBC) were analysed.ResultsDespite the strong multidrug-resistant nature of the pathogens, CFS displayed a moderate antibacterial activity against most tested strains. The acidic nature of the CFS, combined with bioactive antibacterial metabolites like Kanzonol V and 1-Hexanol, likely contributed to its inhibitory effects against pathogenic bacteria; notably, Kanzonol V was abundant in the CFS of L22F, BF12 and BYF26 (L22F_CFS, BF12_CFS and BYF26_CFS), while 1-Hexanol was particularly enriched in CFS of P72N (P72N_CFS), with both compounds effectively targeting bacterial cell membranes to disrupt cell integrity, leading to bacterial cell death. Other beneficial compounds such as Pyroglutamylleucine, Trigoneoside VIII and 18-Nor-4(19),8,11,13-abietatetraene which are likely to have anti-inflammatory, antimicrobial and antioxidant activities, were also detected in the CFS. The CFS-NLCs maintained their antibacterial activity and 30–60% dilutions of product completely inhibited the growth of pathogen strains even after three-months storage at room temperature.ConclusionThese findings suggest that CFS-NLCs could be a promising biotic therapy for treating hospital infections such as canine dermatitis and otitis caused by multidrug-resistant P. aeruginosa and S. pseudintermedius.